2021
DOI: 10.1111/bre.12636
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons record the evolution of the Cathaysian Coastal Mountains along the South China margin

Abstract: Changes in paleogeography are the first-order expression of geodynamics and plate tectonics that strongly influence paleocirculation and global climate models (van Hinsbergen & Boschman, 2019). An Andean-type South China margin formed by the subduction of the Paleo-Pacific Plate during the Jurassic-Cretaceous (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 66 publications
(97 reference statements)
1
4
0
Order By: Relevance
“…The 206 Pb/ 238 U weighted mean eruption/deposition age from 51 spot analyses is 106.6 ± 0.3 Ma (Figures 4b and Table S1 in Supporting Information S1), which is compatible with the late‐Early Cretaceous age based on ostracoda and charophyte fossils (Wang, et al., 1991), sporopollen assemblages (Huang & Long, 2008), and the youngest detrital zircon age (∼120 Ma; Jiang et al., 2015) obtained from the Lumuwan Formation in the Ledong‐Baisha area. The youngest detrital zircon ages in Lumuwan red beds are 105.7 ± 2 Ma in Baisha (19.4°N, 109.7°E) and 108.3 ± 2.8 Ma in Qionghai (19.1°N, 110.4°E; Chen et al., 2021), which are compatible with the tuff age of 106.6 ± 0.3 Ma in Ledong.…”
Section: Geochronologysupporting
confidence: 54%
“…The 206 Pb/ 238 U weighted mean eruption/deposition age from 51 spot analyses is 106.6 ± 0.3 Ma (Figures 4b and Table S1 in Supporting Information S1), which is compatible with the late‐Early Cretaceous age based on ostracoda and charophyte fossils (Wang, et al., 1991), sporopollen assemblages (Huang & Long, 2008), and the youngest detrital zircon age (∼120 Ma; Jiang et al., 2015) obtained from the Lumuwan Formation in the Ledong‐Baisha area. The youngest detrital zircon ages in Lumuwan red beds are 105.7 ± 2 Ma in Baisha (19.4°N, 109.7°E) and 108.3 ± 2.8 Ma in Qionghai (19.1°N, 110.4°E; Chen et al., 2021), which are compatible with the tuff age of 106.6 ± 0.3 Ma in Ledong.…”
Section: Geochronologysupporting
confidence: 54%
“…This inference of the pre‐Oligocene coastal mountains is also supported by palaeo‐altimetric reconstructions and palaeo‐drainage evolution studies. Palaeocurrent and detrital provenance studies of Late Cretaceous and Palaeogene fluvial deposits in sedimentary basin located east and west of the modern coast suggested a drainage system originating from the coastal mountains (Chen et al, 2022; Tian et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward the Okhotomorsk Block drifted northward and collided with the Siberian Craton at ∼80 Ma (Suo et al., 2020; Yang, 2013), the subduction zone of the paleo‐Pacific Plate also retreated eastward during the Late Cretaceous (Li et al., 2019), and Southeast China underwent regional extension (Suo et al., 2019). This tectonic setting is not favorable for the maintenance of such a high range, but the coastal mountains were still >2 km high during the Late Cretaceous (Chen et al., 2022; Zhang et al., 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Reconstructions suggested that a meridionally oriented mountain range had existed along the East Asian coast during the Late Cretaceous (Chen, 2000), and that it had attained an altitude of much more than 2 km in the early Late Cretaceous and became lower afterward (Chen et al., 2022; Zhang et al., 2016). Therefore, it is likely that the strong signal of orbital forcing in the Songliao Basin was due to the East Asian coastal mountains.…”
Section: Introductionmentioning
confidence: 99%